STRATEGIC MOTIVATIONS OF AUSTRALIAN AND NEW ZEALAND MANUFACTURING FOREIGN DIRECT INVESTMENTS IN INTERNATIONAL MARKETS - Rizwan Tahir; Chen Weijing (Asian Academy of Management Journal, 2011)
We empirically investigate how different location-specific variables and strategic motives influenced Australian and New Zealand (ANZ) firms' ownership strategy choices in foreign markets between 1998 and 2008. This study is the first to analyse how strategic motives and ownership-specific, location-specific, and internalisation variables have influenced the ownership structure choices of ANZ firms in foreign markets. The results indicate that large market potential and low levels of cultural distance increase the probability that ANZ manufacturing firms will undertake wholly owned subsidiary (WOS) ownership structures and market-seeking (MS) and/or efficiency-seeking (ES) foreign direct investment (FDI). Low exchange rate fluctuation increases the probability that ANZ manufacturing firms will undertake WOS-type risk reduction-seeking (RRS) FDI.